Analysis of vehicular traffic flow of main road and alternative road in Kuala Terengganu / Nur Aribah Farzana Arifen & Nur Aiman Salsabila Hashim - Arifen, Nur Aribah Farzana; Hashim, Nur Aiman Salsabila (2019)
Nowadays, school traffic congestion has been a major problem in most cities around the world. Vehicular traffic congestion occurs when a large number of vehicles are overcrowded on the road and the traffic flow does not run smoothly. Traffic congestion causes chaos on the road and interruption to daily activities of users. This research aimed to develop solutions for congestion during peak hours in schools. Peak hours is the time where this traffic congestion occurs nearby school. Traffic become slower in peak hours because parents dropping off and picking up their children at school. In this paper, we will analyse the vehicular traffic flow on main road and alternative road in Kuala Terengganu. Binary integer programming and simplex method will be used to analyse traffic congestion at school areas in Kuala Terengganu. This method will give the alternatives road to avoid traffic areas. A MATLAB program will be used to solve Binary Integer Programming. The result will show the binary variable 0 and 1 which variable 1 means the nodes which are affected areas by traffic nearby schools and 0 means free traffic areas.